Efeito do “Continuous positive airway pressure” (CPAP) e do Aparelho Intraoral de avanço mandibular (AIOam) nos parâmetros cardiovasculares da Apneia obstrutiva do sono de grau leve. - Silveira, Thais de Moura Guimarães [UNIFESP] (2020)
Objectives: To evaluate and compare the effects of Continuous Positive Airway Pressure (CPAP), mandibular advancement device (MAD) and no treatment on 24-h ambulatory blood pressure monitoring (24h-ABPM) and peripheral arterial tonometry (PAT) at 6 and 12 months follow-up in individuals with mild Obstructive Sleep Apnea (OSA), and in subgroups with presence of daytime sleepiness, hypertension, or non-dipping pattern at baseline, or who had an AHI of < 5 and adherence ≥ 4 hours per night (effective treatment subgroups). Methods: The inclusion criteria were individuals with mild OSA, any gender, aged between 18 and 65 years, and Body Mass Index (BMI) ≤ 35Kg/m2 . Patients were randomized to CPAP, MAD and no-treatment groups. The evaluations included physical examination, full polysomnography, 24-h ABPM and PAT at baseline, after 6 and 12 months. The GLMM test was used for comparisons. Results: 79 volunteers were included, 31 in the CPAP group, 25 in the AIOam group and 23 in the control group. The CPAP and MAD groups had lower AHIs than the control group at 6 and 12 months (CPAP: 1.7 ± 14.2; MAD:3.8 ± 12.6; control: 9.3 ± 5.2). The MAD group had more hours of treatment per night and better adaptation to treatment than the CPAP group (MAD: 5.7 ± 2.7 h/per night; CPAP: 3.8 ± 3.4 h/per night; MAD: 16% did not adapt; CPAP: 42% did not adapt). No differences were found in the total sample and effective treatment in relation to PAT or 24-h ABPM outcomes. Conclusion: Treatment of mild OSA with CPAP or MAD did not improve BP or endothelial function after one year, even in patients with associated daytime sleepiness, hypertension, non-dipping pattern or in effective treatment.